Dynamic participation processes for policy packaging in transport backcasting studies. (August 2017) - Soria-Lara, Julio A.; Banister, David
Abstract: Scenario analysis is particularly useful when major changes are required to reach climate change goals over a longer time period. Backcasting provides one approach to develop policy packages that together will help achieve these objectives, but one missing element has been the role that stakeholder engagement can play in the identification of suitable policy measures, in the packaging process, and in determining the suitability, the feasibility and the timescale involved. This paper develops a novel dynamic participatory process to address the policy-implementation gap through the engagement of practitioners, policy makers and researchers in a series of workshops that allow these issues to be discussed in an open deliberative process. The spatial context taken is the Andalusia region (Spain), where there is a clear policy desire to implement a sustainable transport strategy for 2050. The paper outlines the methodological process, the development of the policy pathways, the dialogue process, the refinement of the policy pathways, the final strategy, and it then reflects on the usefulness of stakeholder engagement in the policy formulation process. Highlights: It presents a novel dynamic participatory process for policy implementation. It shows the refinement of policy pathways using dialogue spaces. It reflects on the usefulness of stakeholder engagement.